Pengaruh Promosi dan Persepsi Kemudahan Terhadap Keputusan Penggunaan Marketplace Shopee (Studi Pada Pengguna Marketplace Shopee di Jakarta Utara) - Nur Fitri Rahmawati; Ade Firmansyah; Alfihani Alfihani (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine how much influence promotion and perceived convenience have on the decision to use the shopee marketplace (a study on shopee users in North Jakarta, especially in the Kalibaru sub-district). The gaps in this study are promotions by shopee too often and monotonous concepts, the shopee registration process that is not understood by consumers, the lack of attractive promotions compared to other competitors. The research method used in this study is a quantitative method. The data collection technique is in the form of a questionnaire. The population in this study were internet users who had shopped online at least once at Shopee in North Jakarta, especially in the Kalibaru sub-district. The sampling technique for this study used purposive sampling, namely internet users who had shopped online at least once at Shopee. The results of this study indicate that the coefficient of determination of the value of R Square Promotion is 0.506 which indicates that the proportion of influence of the promotion variable on the decision to use is 50.6%. The result of the coefficient of determination of the R Square value of perceived convenience is 0.540 which shows that the proportion of the influence of the variable perceived ease of use is 54.0% The result of the coefficient of determination of the R Square value of promotion and perceived convenience is 0.627 which shows that the proportion of the influence of the promotion variable and the perceived ease of decision usage of 62.7% while the remaining 37.3% is influenced by other factors outside the regression model analyzed.